2012
DOI: 10.1155/2012/627278
|View full text |Cite
|
Sign up to set email alerts
|

Erectile Dysfunction and Hypertension: Impact on Cardiovascular Risk and Treatment

Abstract: Erectile dysfunction (ED) is a common complaint in hypertensive men and can represent a systemic vascular disease, an adverse effect of antihypertensive medication or a frequent concern that may impair drug compliance. ED has been considered an early marker of cardiovascular disease. The connection between both conditions seems to be located in the endothelium, which may become unable to generate the necessary dilatation in penile vascular bed in response to sexual excitement, producing persistent impairment i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
50
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 98 publications
(133 reference statements)
6
50
0
1
Order By: Relevance
“…Since vascular changes in hypertension are well correlated with different organic injuries leading to diseases, including erectile dysfunction 22 , it is highly presumptive that the very delicate germinal epithelium may also be affected by this systemic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Since vascular changes in hypertension are well correlated with different organic injuries leading to diseases, including erectile dysfunction 22 , it is highly presumptive that the very delicate germinal epithelium may also be affected by this systemic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Responses to each of the 5 items of SHIM were rated from 1 to 5 and summed to produce a total score ranging from 5 to 25, with higher scores indicating a better sexual function. According to the scores, patients with ED were categorized into the following 4 grades: no ED (22)(23)(24)(25), mild ED (12)(13)(14)(15)(16)(17)(18)(19)(20)(21), moderate ED (8)(9)(10)(11), and severe ED (5-7). EHS is a reliable single-item scale ranging from 0 to 4: whenever sexual stimulation occurs as EHS0, penis does not enlarge; EHS1, penis is larger but not hard; EHS2, penis is hard but not hard enough for penetration; EHS3, penis is hard enough for penetration but not completely hard; EHS4, penis is completely hard and fully rigid.…”
Section: Main Outcome Measuresmentioning
confidence: 99%
“…Men with hypertension and CHD are shown to have high prevalence of ED and demonstrated good responsiveness and tolerability to sildenafil. 24,25 Hypertension, CHD, and ED shared common physical pathogenesis including endothelial dysfunction and reduced nitric oxide activity. 24,26 And emerging studies suggested that ED might be one of the first signs of cardiovascular problems.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Diabetes and hypertension are both associated with the presence of ED, and it has been stated that ED in hypertensive patients reflects a deterioration of endothelial function and should be seen as an early sign of progressive vascular disease. 22,23 Abnormal corporal smooth muscle cells and generalized fibrosis in the arterial media of small as well as large arteries were found in type 2 diabetic rat models 5 months after the onset of hyperglycemia and may partly explain the mechanism behind diabetes-related ED. 24 The observed correlations between plasma fibulin-1, cardiovascular risk factors and the presence of ED found in this study support the emerging evidence that plasma fibulin-1 has a potential as biomarker for the progression of vascular disease in diabetes.…”
Section: Discussionmentioning
confidence: 99%